A brand-new stethoscope for John Keats - Borghi, Luca (Medicina Historica, 2021)
The bicentenary of John Keats' death is approaching (February 2021) and it deserves a celebration both in the literary and in the medical world. Keats spent in Rome his last months looking for relief from the disease that was killing him: tuberculosis. The physician who took him in charge was the then young Sir James Clark (1788-1870) who, during a stay in Paris in 1819, had become an early and strong supporter of Laennec’s stethoscope. He surely brought some version of it to Rome and most probably used it to auscultate Keats’ lungs. That was not sufficient to prevent the young poet’s death. Nonetheless, Keats became an unaware and unfortunate instrument to that first diagnostic step forward in the titanic medical struggle against “consumption”. As Clark stated in 1820, defending the stethoscope from critics: “To know the nature and extent of a disease is surely the first step in our progress to the adoption of rational means of cure”.